Desain Prototype Robot Vacuum Cleaner Otomatis Berbasis Arduino Uno - Dhoni Hidayatullah; Diva Adesta Putra Afrizen; Maria Ulfa; Muhammad Fairuz Ivandyaputra; Sheva Maulana Ardy Syah Putra; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2024)
The Arduino Uno-based Robot Vacuum Cleaner has been created as an innovative solution to deal with the problem of difficulty in cleaning the floor. Instead of traditional methods such as sweeping or using a large vacuum cleaner that require time and effort, this robot can be operated efficiently through Arduino Uno automatic control. By utilizing Arduino Uno, the robot is able to perform various functions automatically, including moving forward, backward, turning right, and turning left, while sucking up dirt independently. Through the test results, it was found that this robot vacuum cleaner can vacuum dust and garbage thoroughly. In addition, it can operate without error for 3 hours on a full battery, demonstrating reliable and efficient performance.